ANALISIS TINDAK TUTUR ILOKUSI IKLAN PERDAGANGAN DI RADIO HARAU FM PAYAKUMBUH PERIODE PEBRUARI-APRIL 2016 - Novianti, Hasmi (BAHASTRA, 2017)
Using advertising as a persusif medium is a relative effective way to convey informations. Tells reader how ads or advertisement of speech may also affect consumer, this making consumer interested in buying the products offered. This study aimed to describe the type-the type of speech act ilukusi ads Harau FM radio trade in the period Februari-April 2015. This is a type of qualitative research by using descriptive method. Method and techniques of data colletions is done by methode refer. Research listened then record trade advertising in Harau FM radio. Intrument is the researcherâs own research and assisted with phone or mobile phone to record a trade ad in Harau FM radio. Methods and techniques of data analysis is by using unified method, this method uses aggregated pragmatic power engineering. Analyzing is done through a procedure, thorough the tabulation, the table used adjusted to focus research problem, deepening used to obtain a more focused overview accordance with the problem. Based on analysis of data 21 utterances ads are ads Harau trade in FM radio. Assertive illocutionary speech acts found in 21 data consists of 10 acts assertive told, 10 acts assertive asserted, and the fist follow-assertive suspect. From 13 directive speech acts. Found 5 acts directive shout , 6 follow the directive requested, and two follow-directive forbids. From 17 commissive speech act, found 9 acts commissive propose, and 8 follow commisive offer, and 1 follow-commisive promised. From 8 declarative speech act. Found 1 acts declarative decided, and 3 follow declarative sentense. From 8 speech acts expressive, expressive acts complained discovered 2, 3 acts of expressive angry, 3 actsadvertising trade FM radio Harau the period February-April 2015 more predominant use of assertive illocutionary speech act.